2018
DOI: 10.1039/c8tc03014f
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient white quantum dot light-emitting diode employing magnesium doped zinc oxide as the electron transport layer based on bilayered quantum dot layers

Abstract: A highly efficient QLED achieving white emission at a low driving voltage is obtained by employing Zn0.95Mg0.05O as the electron transport layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…Magnesium-doped ZnO quantum dots have also been used as the electron transport layer in a layered LED made completely out of functional quantum dot layers. 172 Very recently, a CdSe/CdS/ZnS quantum dot LED has also been reported with a sol-gelsynthesized ZnO film as a highly conductive electron transport layer. 173 The use of ZnO quantum dots for making LEDs is an interesting development.…”
Section: Zno Quantum Dot Ledsmentioning
confidence: 99%
“…Magnesium-doped ZnO quantum dots have also been used as the electron transport layer in a layered LED made completely out of functional quantum dot layers. 172 Very recently, a CdSe/CdS/ZnS quantum dot LED has also been reported with a sol-gelsynthesized ZnO film as a highly conductive electron transport layer. 173 The use of ZnO quantum dots for making LEDs is an interesting development.…”
Section: Zno Quantum Dot Ledsmentioning
confidence: 99%
“…Copyright 2018, Royal Society of Chemistry. (f) Device structure of the B/Y-QD-bilayered WQLEDs [38]. Reprinted with permission from ref.…”
Section: Wqleds With a Mixed-qd Single Emlmentioning
confidence: 99%
“…The emission color of the presented WQLEDs was still unstable as the driving voltage was changed (Figure 3(e)), which was mainly caused by the migration of the exciton recombination zone. Recently, Chen et al reported conventional WQLEDs with a Y/B QD bilayered EML and with a higher CE of 24.6 cd/A (Figure 3(f)) [38]. In this device, the same ZnO nanoparticles were employed as a buffer layer to prevent the under-QD layer from being damaged by the solvent of the upper QDs.…”
Section: Wqleds With a Multilayered Emlmentioning
confidence: 99%
“…1 It is an n-type II-IV semiconductor possessing a wide band gap (3.37 eV) and large exciton binding energy (60 meV). 2 These valuable properties make ZnO an excellent candidate for optoelectronic applications including solar cells, [3][4][5][6][7] transparent conducting oxides (TCO), [8][9][10] light emitting diodes (LEDs), [11][12][13] ultraviolet (UV) lasers, 14,15 and photodetectors. 16,17 More specifically for solar cells, nanostructured ZnO can serve as an electron-transporting layer (ETL) or transparent conductive electrode (TCO) owing to its inherent high electron mobility and high conductivity.…”
Section: Introductionmentioning
confidence: 99%